2019
DOI: 10.1021/acs.jpclett.9b01053
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Mapping of Thermal Conductivity, Thermal Diffusivity, and Volumetric Heat Capacity of Halide Perovskite Thin Films: A Novel Nanoscopic Thermal Measurement Technique

Abstract: Local thermal conductivity, thermal diffusivity, and volumetric heat capacity of all-inorganic halide perovskite thin films are mapped simultaneously and with highest spatial resolution for the first time. These various thermal properties are detected by a scanning near-field thermal microscope operated at two different frequencies simultaneously. We apply this technique to analyze the thermal properties of halide perovskites on the nanoscale. In addition to an ultralow thermal conductivity of 0.43 ± 0.03 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…An initial study by backscattered scanning electron microscopy (SEM) revealed a notable contrast ( figure 1(b)). Note, a similar contrast has previously been evidenced by electron backscatter diffraction (EBSD) for Cs x Pb y Br z perovskite thin films that had undergone a similar procedure [2,32], where the contrast could be clearly assigned to CsPbBr 3 (3D) and CsPb 2 Br 5 (2D) grains in the film. In the present case, the coexistence of 3D phase CsPbCl 3 and the 0D phase Cs 4 PbCl 6 has been confirmed by XRD ( figure 1(c)).…”
Section: Mapping Thermal Properties Of Cs X Pb Y Cl Z Perovskite Thinsupporting
confidence: 74%
See 4 more Smart Citations
“…An initial study by backscattered scanning electron microscopy (SEM) revealed a notable contrast ( figure 1(b)). Note, a similar contrast has previously been evidenced by electron backscatter diffraction (EBSD) for Cs x Pb y Br z perovskite thin films that had undergone a similar procedure [2,32], where the contrast could be clearly assigned to CsPbBr 3 (3D) and CsPb 2 Br 5 (2D) grains in the film. In the present case, the coexistence of 3D phase CsPbCl 3 and the 0D phase Cs 4 PbCl 6 has been confirmed by XRD ( figure 1(c)).…”
Section: Mapping Thermal Properties Of Cs X Pb Y Cl Z Perovskite Thinsupporting
confidence: 74%
“…The thermal measurement methodology is described in detail in [32]. Briefly summarized, the resistive thermal probe of the SThM (VITA-SThM probe from Bruker) is powered by a mixed signal of an adder at two AC currents I 0 1 sin(ω 1 t) and I 0 2 sin(ω 2 t) with angular frequencies ω 1 and ω 2 .…”
Section: Measurement Methodologymentioning
confidence: 99%
See 3 more Smart Citations